The Effect of Several Types of Refugia Plants on Whitefly Populations and Production of Red Chili Varieties (Capsicum Annum L.) - Jasmi; Sumeinika Fitria Lizmah; Aisyah, Cut (Jurnal Online Pertanian Tropik, 2024)
The purpose of this study was to measure the effect of refugia on the whitefly population and the production of several varieties of red chili (Capsicum annum L.). This research was conducted in the experimental garden of the UTU Faculty of Agriculture, West Aceh Regency from March - June 2019. Materials used: TM 999 chili seeds, Lado F1 variety, F1 Lidia variety, NPK fertilizer, manure, Kenikir flower plants, Zinnia flowers, and polybags. Tools used: hoe, hand sprayer, camera, and stationery. This study used a 3x2 split plot design with 3 replications. The factor studied was the presence of a whitefly. As the main plot, Refugia (R) consists of three levels, namely R0 = Control, R1 = Zinnia, and R2 = Thinking. Variety (V) consists of 3 levels, namely V1 = TM 999, V2 = Lado F1, and V3 = Lidia F1. The variables observed were the calculation of whitefly population, the percentage of attack rate, and production per plot. The results showed that Refugia plants had a very significant effect on the whitefly population, percentage of pest attack rates, and production per plot. Variety has a significant effect on the percentage level of pest attacks and production per plot.